Locomotion modulates specific functional cell types in the mouse visual thalamus - Çağatay Aydın (Nature Portfolio, 2018)
Locomotion is known to modulate neuronal firing in both the visual thalamus (LGN) and V1. Here, the authors characterize the LGN modulation in detail and report that neurons with transient ON responses for high spatial frequency stimuli show the strongest gain modulation.